Ion transport on phased radiofrequency carpets in xenon gas - E. Dey; B. J. P. Jones; Y. Mei; M. Brodeur; V. A. Chirayath; N. Coward; F. W. Foss; K. E. Navarro; I. Parmaksiz; C. Adams; H. Almazán; V. Álvarez; et al. (European Physical Journal C: Particles and Fields, 2025)
Abstract We present the design and performance of a four-phased radiofrequency (RF) carpet system for ion transport between 200–600 mbar, significantly higher than previously demonstrated RF carpet applications. The RF carpet, designed with a 160  $$\upmu $$ μ m pitch, is applied to the lateral collection of ions in xenon at pressures up to 600 mbar. We demonstrate transport efficiency of caesium ions across varying pressures, and compare with microscopic simulations made in the SIMION package. The novel use of an N-phased RF carpet can achieve ion levitation and controlled lateral motion in a denser environment than is typical for RF ion transport in gases. This feature makes such carpets strong candidates for ion transport to single ion sensors envisaged for future neutrinoless double-beta decay experiments in xenon gas.